PERBANDINGAN BAKTERI KONTAMINAN PADA LALAT Chrysomyia megacephala DAN Musca domestica DI TEMPAT PEMBUANGAN SAMPAH AKHIR PIYUNGAN, BANTUL, YOGYAKARTA - Retno . Hestiningsihr (Jurnal Kesehatan Masyarakat Indonesia, 2004)
ABSTRACT Background: Flies are mechanical vector of several gastrointestinal diseases agents, either caused by Parasites or bacteria. Flies are contaminated by microbes from rubbish in garbage collection sites (final garbage disposal). Objectives: (l) Identifying the species of bacteria on flies which associated with human in final garbage disposal; (2) To count and analyze the intensity of pathogenic bacteria on the flies. Method: Flies were collected by net and fly trap in Final Garbage Disposal. Then, the flies species were identified. Otherwise, bacteria were isolated using TCBS and it was identified by MacConkey Method. Results: Chrysomyia magacephala is the dominant species fly found at the garbage collection sites. Bacteria E. coli, Klebsiella pneumonia, Bacillus spp and Entrobacter aero genes contaminated flies in high number. Conclusion: C megacephala is the dominant species of fly, only E coli the bacteria cause of gastrointestinal diseases was found, fly were contaminated by microbes from rubbish. Keywords : Chrysomyia megacephala, Musca domestic a, Bacteria contaminants